Experimental Study on the Seismic Performance of a Partition Damped Wall-Filled Frame Structure - Shuainan Zhai; Zuyin Zou; Zhanyuan Zhu; Zixing Zhang; Wei Liang; Xuanhao Cheng; Shuzhen Chang (Shock and Vibration)
In the past, earthquakes have caused significant damage to traditional masonry filler wall frame structures. To solve this problem, a new design scheme, the partition damping filler wall, is proposed in this paper to reduce the interaction between the filler wall and the frame structure. Low cyclic loading tests are carried out on the traditional and the new masonry filler wall frames. Besides, one full-scale-angled span layer frame without a filler wall is produced for comparison analysis. The mechanical performances of the different frames are studied, including the characteristics of the deformation failure modes, hysteretic curves, skeleton curves, rigidity degeneration, energy dissipation capacity, and the lateral displacement of the frame columns. The research results show that the partition damping filler wall can significantly decrease the diagonal bracing effect of the filler wall on the steel frame. Meanwhile, the setting of the low-strength mortar between the filler wall and steel frame and the arrangement of the damping layer can improve the stress distribution and delay the crack development of the wall. Furthermore, the stiffness degradation rate of the partition damping filler wall is obviously slower than that of the traditional masonry filler wall frame structure. In this paper, the partition damped wall-filled frame structure shows outstanding ductility and deformation capacity.